Perencanaan Prioritas Lokasi TPA Khusus Kawasan Perkotaan (Studi Kasus : Kabupaten Bandung Barat) - Rita Sri Rejeki Panjaitan; Zefri Zefri; Irwan Prasetyo (Jurnal Kajian Wilayah dan Kota, 2022)
The purpose of this study is to determine the priority areas for waste services in West Bandung Regency. This research uses quantitative research methods. In practice, this research method emphasizes the use of numbers and uses several supporting methods, namely qualitative and descriptive methods. In the process of determining the priority plan for solid waste services, there are two approaches taken, namely analysis of the distribution and number of waste facilities needs and analysis of the scale of interest of the waste facility service area. Based on the results of the analysis of Gununghalu District with a final score of 27, while Cipeundeuy and Cipongkor Districts with a final score of 18. The greater the value obtained indicates that Gununghalu District deserves to be a landfill area.